Implementation of accrual based International Public Sector Accounting Standards (IPSAS) in the local government authorities: A case of Dodoma region - Matekele, Charles K. (Mzumbe University, 2024)
A dissertation report submitted in partial/fulfillment of the requirement for award of Degree of Master of Science in Accounting and Finance (MSc. A & F) of Mzumbe University